Affordability of Healthy and Sustainable Diets in Nigeria - Mekonnen, Daniel A.; Akerele, Dare; Achterbosch, Thom; de Lange, Thijs; Talsma, Elise F. (Frontiers in Sustainable Food Systems, 2021)
This study examines the cost and affordability of healthy diets in Nigeria. Using the 2015/16 and 2018/19 waves of Nigeria General Household Surveys, we find that, generally, the least-cost options to meet dietary recommendations for vegetables, dairy, and protein-rich foods are more expensive to meet than that of other food groups. Despite improvements during the survey years, the challenges of affordability of healthy diets appear more pronounced in rural than urban, among poorest household groups, and in northern than southern Nigeria. Results suggest that it will be more expensive to meet the dietary recommendation for dairy foods if priority will be given for food systems sustainability over concerns for food preferences of the households. It will however be cheaper to achieve dietary recommendations for vegetables, fruits and starchy staples even when households give more consideration to food systems sustainability than tastes and preferences in their choice of healthy foods. Relative affordability of protein-rich foods are less affected by whether (or not) tastes/preferences or food systems sustainability drives healthy food choices. Key implication is that interventions targeting on affordability of healthy diets should give greater attention to the poorest of the poor, to rural than urban, and to northern than southern Nigeria. Implications relevant for research, policy, and other actors that focus on transformation of the food systems toward achieving healthier diets in a sustainable food systems are discussed.